2022
DOI: 10.3389/fnhum.2022.910669
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Values of Changes in Local and Remote Brain Functional Connectivity in Primary Angle-Closure Glaucoma Patients According to Support Vector Machine Analysis

Abstract: PurposeThe primary angle-closure glaucoma (PACG) is an irreversible blinding eye disease in the world. Previous neuroimaging studies demonstrated that PACG patients were associated with cerebral changes. However, the effect of optic atrophy on local and remote brain functional connectivity in PACG patients remains unknown.Materials and MethodsIn total, 23 patients with PACG and 23 well-matched Health Controls (HCs) were enrolled in our study and underwent resting-state functional magnetic resonance imaging (rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In previous studies, SVM have been integrated with rs-fMRI to achieve optimal predictive results for lesion classification by identifying patients and HCs based on abnormal signal values. 44–48 Therefore, we applied the SVM approach to test whether abnormal WM function can effectively differentiate PACG patients from HCs.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, SVM have been integrated with rs-fMRI to achieve optimal predictive results for lesion classification by identifying patients and HCs based on abnormal signal values. 44–48 Therefore, we applied the SVM approach to test whether abnormal WM function can effectively differentiate PACG patients from HCs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, resting-state functional MRI (rs-fMRI) has been increasingly used to explore intrinsic brain activity in glaucoma patients and has provided critical information in the search for pathological mechanisms ( 14 , 15 ). Several recent studies have shown that PACG patients exhibit abnormalities in regional homogeneity (ReHo) ( 16 , 17 ) and amplitude of low-frequency fluctuation (ALFF) ( 18 , 19 ) in multiple brain regions. And Tong et al ( 20 ) found that there is disturbed interhemispheric resting-state functional connectivity in the vision-related brain areas of individuals with PACG.…”
Section: Introductionmentioning
confidence: 99%